Impact of Playing Game Online on the Learning Motivation of Grade V Elementary School Students in the Subject of Pancasila Education: Case Study at AL-Madani Prima Elementary School, Sub-district Ciparay Bandung Regency - Nadhifah, Hanin Marwa; Reviyanti, Lysda; Istiqomah, Rizki Alita (Pancasila International Journal of Applied Social Science, 2025)
This study aims to analyze the impact of online games on fifth-grade students' learning motivation in Pancasila Education subjects at SD AL-Madani Prima, Ciparay District, Bandung Regency. The background of this study is based on the phenomenon of increasing intensity of playing online games among elementary school students which is suspected of having an impact on decreasing learning motivation. The study used a qualitative approach with a case study method, involving 30 students, 2 Pancasila Education teachers, and 6 parents of students as participants. Data were collected through observation, in-depth interviews, and documentation, and analyzed using NVivo 14 software. The results showed that most students had the habit of playing online games every day for a fairly long duration, especially on weekends. The negative impacts found included decreased learning concentration, reduced time to do assignments, and decreased participation in learning. However, there were also positive impacts, such as increased cooperation and problem-solving skills in some students. The role of teachers and parents is very important in managing this habit through limiting playing time, an interesting pedagogical approach, and intensive communication. It is recommended that schools implement gamification-based learning strategies to increase students' learning motivation. This study provides important insights for schools, teachers, and parents in managing the influence of online games on learning and designing educational interventions that are more adaptive to technological developments.